Securitizing youth : young people's roles in the global peace and security agenda. - Ensor, Marisa O. (Rutgers University Press, 2021)
"Securitizing Youth offers new insights on young people's engagement in a wide range of contexts related to the peace and security field. It presents empirical findings on the challenges and opportunities faced by young women and men in their efforts to build more peaceful, inclusive, and environmentally secure societies. The chapters included in this edited volume examine the diversity and complexity of young people's engagement for peace and security in different countries across the globe and in different types and phases of conflict and violence, including both conflict-affected and relatively peaceful societies. Chapter contributors, young peacebuilders, and seasoned scholars and practitioners alike propose ways to support youth's agency and facilitate their meaningful participation in decision-making. The chapters are organized around five broad thematic issues that correspond to the 5 Pillars of Action identified by UN Security Council Resolution 2250. Lessons learned are intended to inform the global youth, peace, and security agenda so that it better responds to on-the-ground realities, hence promoting more sustainable and inclusive approaches to long-lasting peace"--